Organizational citizenship behaviors under theory of servant leadership: A exploratory study in a sample of faculties of the University of Alqadisiya - رشيد, صالح عبد الرضا; مطر, ليث علي (Journal of Economics and Administrative Sciences, 2014)
This study aimed to identify the role of servant leadership in promoting organizational citizenship behaviors in a sample of faculties of the University of Alqadisiya .It tried to answer several questions represented its problem.   The most important questions are the followings:1- Is there enough perception among administrative leaders in the aforementioned faculties toward the concept of servant leadership? And under what level?                                                  2 - Is there enough perception among administrative leaders in those faculties toward organizational citizenship behavior? What is its level? 3 - Is there a relationship between servant leadership and organizational citizenship behaviors? What is the nature of this relationship? 4 - Is there a statistically significant effect of servant leadership in organizational citizenship behaviors?    The researchers adopted  the descriptive   approach to analyze views of a sample of (287) department heads and faculty members in six out of eleven faculties of the University. The researchers used the questionnaire to measure the study variables to measure the variables of the study .They also used a set of necessary statistical methods and  programs to test its hypotheses and then achieve its objectives, which showed a statistically significant correlation and  effect between servant leadership style and organizational citizenship behavior.                                                                           In light of the findings emerged from the study, the researchers have made a set of recommendations in the forefront of them is  the importance of servant leadership in promoting organizational citizenship behaviors to achieve objectives of educational institutions, and establish the concept of service and compassion among members of faculties  and to create a climate that encourages service and personal assistance, as well as developing  training programs for administrative leadership to ensure   the concept of service to them.